2018
DOI: 10.1038/s41598-017-18179-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of bones, mites, soil chemistry, nematodes and soil micro-eukaryotes from a suspected homicide to estimate the post-mortem interval

Abstract: Criminal investigations of suspected murder cases require estimating the post-mortem interval (PMI, or time after death) which is challenging for long PMIs. Here we present the case of human remains found in a Swiss forest. We have used a multidisciplinary approach involving the analysis of bones and soil samples collected beneath the remains of the head, upper and lower body and “control” samples taken a few meters away. We analysed soil chemical characteristics, mites and nematodes (by microscopy) and micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 68 publications
1
50
0
6
Order By: Relevance
“…These processes include gross postmortem changes (e.g., livor mortis, marbling, bloating), autolysis, putrefaction, insect larval development, scavenging activity, and many others. Taphonomy is relevant to medicolegal death investigation because proper interpretation of decomposition processes can accomplish investigative goals such as establishing the cause of death , locating clandestine graves , and estimating postmortem interval . An ecological approach to studying and applying taphonomy is often implemented because many decomposition processes are biologically mediated.…”
mentioning
confidence: 99%
“…These processes include gross postmortem changes (e.g., livor mortis, marbling, bloating), autolysis, putrefaction, insect larval development, scavenging activity, and many others. Taphonomy is relevant to medicolegal death investigation because proper interpretation of decomposition processes can accomplish investigative goals such as establishing the cause of death , locating clandestine graves , and estimating postmortem interval . An ecological approach to studying and applying taphonomy is often implemented because many decomposition processes are biologically mediated.…”
mentioning
confidence: 99%
“…Recently, several independent studies have demonstrated the applicability of this type of study to the estimation of PMI and have investigated the effects of different hosts (e.g. decomposing human [12][13][14][15][16], swine [17][18][19] or rodents [14,18,20]), different burial conditions (e.g. exposed on the surface [12][13][14][15][16][17][18]20] or shallow burials [15,19]), different environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…decomposing human [12][13][14][15][16], swine [17][18][19] or rodents [14,18,20]), different burial conditions (e.g. exposed on the surface [12][13][14][15][16][17][18]20] or shallow burials [15,19]), different environments (e.g. indoor laboratory environments [14,20] or outdoor environments in different geographical locations [12][13][14][15][16][17][18][19]) and different sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A definição de intervalo post mortem (IPM) diz respeito ao lapso temporal que transcorreu desde a ocorrência do óbito até o momento em que se tem início a análise do corpo ou suas partes disponíveis (SZELECZ, et al 2018). A estimativa do IPM tem seu prelúdio com o exame macroscópico do cadáver ou remanescentes ósseos, observando os aspectos que levam em consideração a aparência macroscópica, preservação do tecido e odor (WOESS, et al 2017).…”
Section: Discussionunclassified
“…O intervalo post mortem (IPM) é o período de tempo desde a ocorrência do óbito até o momento em que se passa a analisar o corpo e/ou seus remanescentes (SZELECZ, et al 2018). A estimativa deste intervalo é assunto de grande relevância no âmbito forense por seu papel importante na resolução de casos criminais.…”
Section: Estimativa De Intervalo Post Mortemunclassified